Kontruksi Hukum Perampasan Aset Dalam Persfektif Economic Analysis of Law - Anang Indrianto (UNES Law Review, 2024)
The author identifies economic factors influencing the development of asset seizure legislation and conducts a literature review on related economic theories and the concept of asset seizure. The study also includes case analyses from various countries to investigate the application of economic theory in the context of asset forfeiture law, viewed from the perspective of economic analysis of law. This research aims to examine the need for regulating the concept of asset seizure without punishment in legislation. Legal analysis incorporating economic concepts is known as economic analysis of law. The study will investigate the economic impact of asset confiscation without conviction, as well as its effect on the effectiveness and efficiency of regulations.While asset seizure has been previously studied from criminal law and human rights perspectives, it has not been extensively examined from the viewpoint of economic analysis of law. Therefore, this research is expected to contribute to the development of economic analysis of law theory and provide a new perspective on asset seizure regulation.